Gut colonization with an obesity-associated enteropathogenic microbe modulates the premetastatic niches to promote breast cancer lung and liver metastasis - Parida, Sheetal; Siddharth, Sumit; Gatla, Himavanth R.; Wu, Shaoguang; Wang, Guannan; Gabrielson, Kathleen; Sears, Cynthia L.; Ladle, Brian H.; Sharma, Dipali (Frontiers in Immunology, 2023)
Background: Obesity, an independent risk factor for breast cancer growth and metastatic progression, is also closely intertwined with gut dysbiosis; and both obese state and dysbiosis promote each other. Enteric abundance of B. fragilis is strongly linked with obesity, and we recently discovered the presence of B. fragilis in malignant breast. Given that enterotoxigenic B. fragilis or ETBF, that secretes B. fragilis toxin (BFT), has been identified as a pro-carcinogenic microbe in breast cancer, it is necessary to examine its impact on distant metastasis and underlying systemic and localized alterations promoting metastatic progression of breast cancer.We used syngeneic mammary intraductal (MIND) model harboring gut colonization with ETBF to query distant metastasis of breast cancer cells. Alterations in the immune network and cytokines/chemokines in the tumor microenvironment and distant metastatic sites were examined using flow cytometry, immunohistochemistry and multiplex arrays.Results: ETBF infection initiates a systemic inflammation aiding in the establishment of the premetastatic niche formation in the vital organs via increased pro-inflammatory and pro-tumorigenic cytokines like IL17A, IL17E IL27p28, IL17A/F, IL6 and IL10 in addition to creating a pro-metastatic, immunosuppressive environment in the liver and lungs rich in myeloid cells, macrophages and T regulatory cells. It induces remodeling of the tumor microenvironment via immune cell and stroma infiltration, increased vasculogenesis and an EMT like response, thereby, encouraging early metastatic dissemination ready to colonize the conducive environment in liver and lungs of the breast tumor bearing mice.In this study, we show that enteric ETBF infection concomitantly induces systemic inflammation, reshapes tumor immune microenvironment, and creates conducive metastatic niches to potentiate early dissemination and seeding of metastases to liver and lung tissues in agreement with the 'seed and soil hypothesis'.Our results also support the ETBF-induced 'parallel model' of metastasis which advocates for an early dissemination of tumor cells that form metastatic lesions independent of the primary tumor load.